Advanced functional materials / Thiolated poly- and oligosaccharide-based hydrogels for tissue engineering and wound healing - Noreen, Sobia; Bernkop-Schnürch, Andreas (Advanced Functional Materials, 2024)
Due to thiolation of poly- and oligosaccharides numerous favorable properties for tissue engineering and wound healing can be introduced. Poly- and oligosaccharides can be thiolated via hydroxyl-to-thiol conversions or the covalent attachment of sulfhydryl ligands to hydroxyl, carbonic acid or amino groups on them. Since thiolated poly- and oligosaccharides can cross-link via disulfide bonds, they form stable 3D networks with defined microarchitecture, stiffness, elasticity, and degradability. Furthermore, thiol groups can enhance cell adhesion since cells exhibit cysteine-rich subdomains on their surface that form disulfide bonds with them. Sulfhydryl groups can also participate in cell signaling pathways favoring various cellular processes like proliferation, migration, spreading, and differentiation that are beneficial for tissue engineering and wound healing. In addition, a controlled release of active ingredients such as growth factors being bound via disulfide bonds to thiolated poly- and oligosaccharides can be achieved via thiol/disulfide exchange reactions. Over the last two decades, the number of thiolated poly- and oligosaccharides such as thiolated hyaluronic acid and thiolated chitosan used for tissue engineering and wound healing has increased tremendously. Within this review, an overview is provided about the chemistry of thiolated poly- and oligosaccharides, their key properties, applications and performance in clinical trials and as marketed products. Version of record